Hubungan Tingkat Pengetahuan Dan Sikap Dengan Kejadian Acne Vulgaris Pada Remaja di SMA Muhammadiyah 02 Medan - Arda Tilla; Hervina Hervina (JURNAL PANDU HUSADA, 2020)
Acne Vulgaris is a skin disease caused by inflammation in the pilosebaseusfollicleAbstract: Acne Vulgaris is a skin disease caused by inflammation in the pilosebaseusfollicle and this is the most common disease in adolescents within aged 15 to 18. Theaesthetic patients usually complained about Acne Vulgaris. There are many factors thatcan make Acne Vulgaris such as ages, ras, hereditary, unbalance of hormonal, stress,food, cosmetic, types of skin, lackage of knowledge and attitude of adolescents. Thepurpose of this study is to determine the relationship between the level of knowledge andattitudes of adolescents at Muhammadiyah 02 Medan High School with the incidence ofAcne Vulgaris. This research used descriptive analytic method with cross-sectional design.The subjects in this study were students from Muhammadiyah 02 Medan High School. Thetechnique in this study was using simple random sampling and data analysis was using thechi square test. Retrieving data through filling in questionnaires. Test about the level ofknowledge of the students of Muhammadiyah 02 Medan High School about Acne vulgarismajority is categorized as sufficient (48.4%) and the results of attitude tests on Acnevulgaris were mostly categorized as good (66.7%). knowledge and attitude with theincidence of Acne vulgaris obtained p -0.877 (p 0.05) and p 0.000 (p 0.05) There wasno relationship between the level of knowledge with the incidence of Acne vulgaris, butthere was relationship between attitude with the incidence of Acne vulgaris. Keywords : acne, teenagers, knowledge, attitudeand this is the most common disease in adolescents within aged 15 to 18. The aesthetic patients usually complained about Acne Vulgaris. There are many factors that can make Acne Vulgaris such as ages, ras, hereditary, unbalance of hormonal, stress, food, cosmetic, types of skin, lackage of knowledge and attitude of adolescents. The purpose of this study is to determine the relationship between the level of knowledge and attitudes of adolescents at Muhammadiyah 02 Medan High School with the incidence of Acne Vulgaris. This research used descriptive analytic method with cross-sectional design. The subjects in this study were students from Muhammadiyah 02 Medan High School. The technique in this study was using simple random sampling and data analysis was using the chi square test. Retrieving data through filling in questionnaires. Test about the level of knowledge of the students of Muhammadiyah 02 Medan High School about Acne vulgarismajority is categorized as sufficient (48.4%) and the results of attitude tests on Acne vulgaris were mostly categorized as good (66.7%). knowledge and attitude with the incidence of Acne vulgaris obtained p -0.877 (p 0.05) and p 0.000 (p 0.05) There was no relationship between the level of knowledge with the incidence of Acne vulgaris, but there was relationship between attitude with the incidence of Acne vulgaris. Keywords : acne, teenagers, knowledge, attitude